A framework for non-contact ECG signal detection device on smart chair and its implementation - Waili, Tuerxun; Mohd Nor, Rizal; Azami Sidek,, Khairul; Abubakar, Adamu; Haruna, Chiroma; Herawan, Tutut (Springer Nature Singapore, 2019)
Heart disease is the top cause of death in Malaysia. Arrhythmia is a sign of heart diseases that entails abnormal heart rhythm and is detected mostly by electrocardiogram (ECG) devices, which are attached to the chest, arms or legs of an individual. This mostly requires contact with the skin, which has to be routinely examined. Unfortunately, in unexpected, extreme situations of rising symptoms related to heart problems, the time it takes to examine a situation with the ECG signal device might make the difference between life and death. Non-contact ECG signal detection techniques could help assess cases of heart problems or an initial apoplectic condition without attaching ECG signal devices to people’s body. This paper aims to provide a non-contact ECG signal detection framework that could empower Malaysian community to get an access to understanding arrhythmic phase status at any time of their activities. The framework relies on one of the major activities that humans often engage in, which is sitting. As a result, a non-contact ECG signal device is conceptualized for chairs that most people can use at home, in the office chair and many other sitting situations